ANALYSIS OF STUDENTS’ ERRORS IN MATHEMATICAL PROBLEM SOLVING BASED ON KASTOLAN ERROR ANALYSIS - Esterlina Esterlina; Jarnawi Afgani Dahlan; Bambang Avip Priatna Martadiputra (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This research is motivated by the many mistakes made by students in solving problem-solving questions. The purpose of this research was conducted to see the causes of student errors in solving problem-solving questions based on kastolan error analysis theory. The research method used is descriptive qualitative. The instrumented object in this study involved 4 students of class XI MIA 5. The sample selection technique uses purposive sampling. The instruments used in this study were tests and interviews.The test results were obtained from a problem-solving ability test through creative problem-solving learning on linear programming material. Based on the results of the many errors found in the indicator, presenting mathematical situations in various ways and knowing the differences, and developing the concepts that have been studied. The types of errors that students have made in answering the problem included conceptual error, procedural error, and technical error